Bio-Analytical Method Development and Validation of Asciminib and its Application to Pharmacokinetic Studies in Rat Plasma by Using RP-HPLC - Sandhya, P.; Nataraj, K. Sri; Vijayalakshmi, R. (Asian Journal of Chemistry, 2023)
The aim of the proposed study was to validate a rapid, uncomplicated, accurate, robust and sensitive bio-analytical method for quantifying asciminib using ivosidenib as an internal standard in rat plasma. This work provides a summary of recent advances in bio-analytical HPLC methodologies employing a Luna phenyl hexyl column (150 × 4.6 mm, 3.5) with an organic mobile phase of potassium dihydrogen phosphate (adjusted to pH 3.0 with orthophosphoric acid) and acetonitrile in the ratio 40:60. With a correlation coefficient of 0.999, the asciminib calibration curve was linear over the range of 100-2000 ng/mL. Using liquid-liquid extraction, the percent of recovered ASB ranged between 97.8 and 99.9%. The plasma stability of the bench-top and auto sampler remained stable for 24 h in the auto sampler. The T1/2 is 5 h and Tmax is 3 h, as calculated from the pharmacokinetic parameters. The application indicates that all parameters of system suitability, specificity, linearity and accuracy are in good agreement with the prescribed limits; consequently, the current method is highly stable, rapid and capable of analyzing plasma samples. This method is ideally adapted for determining asciminib in pure or dose form due to its novel technology.